Some aspects of designing and numerical modelling of glass railing exposed to impact load - Pešek, Ondřej; Melcher, Jindřich (VSB – Technical University of Ostrava, 2022)
In recent architecture glass is widely used structural material of facades, walls, roof, stairs and other applications. Glass as a material is popular for its transparency, but it need to be carefully analysed for its fracture behaviour. This paper deals with some aspects of numerical modelling and designing of all-glass railings acting as cantilever element fixed at the bottom edge and with a handrail on the top edge. In the frame of study, number of different glass railings models were analysed to find out the best way how to simulate glass railing imposed to the impact load. The impact load is in most cases decisive load case acting on that type of structure. Variable parameters entering the analysis are the aspect ratio of glass railing pane, impact intensity, impact member hardness and finite element meshing. Finite element analysis of 250 models was performed in ANSYS Workbench.

In recent architecture glass is widely used structural material of facades, walls, roof, stairs and other applications. Glass as a material is popular for its transparency, but it need to be carefully analysed for its fracture behaviour. This paper deals with some aspects of numerical modelling and designing of all-glass railings acting as cantilever element fixed at the bottom edge and with a handrail on the top edge. In the frame of study, number of different glass railings models were analysed to find out the best way how to simulate glass railing imposed to the impact load. The impact load is in most cases decisive load case acting on that type of structure. Variable parameters entering the analysis are the aspect ratio of glass railing pane, impact intensity, impact member hardness and finite element meshing. Finite element analysis of 250 models was performed in ANSYS Workbench.
Some aspects of designing and numerical modelling of glass railing exposed to impact load
Keywords: Impact load; numerical modelling; pendulum test; railing; structural glass; Impact load; numerical modelling; pendulum test; railing; structural glass